LEZATNYA SAYUR ARES BERBAHAN DASAR BATANG PISANG SEBAGAI MAKANAN KHAS SUKU SASAK DI KABUPATEN LOMBOK BARAT NUSA TENGGARA BARAT - Soebyanto, Oentoeng; Sekarwati, Baiq Anggita; Susanto, Dwiyono Rudi (Kepariwisataan: Jurnal Ilmiah, 2018)
The purpose of this research was to determine strategies in preserving and to introduce sayur ares. This research method using cualitative descriptive analysis and SWOT analysis, which means writing the result of analysis in facts and do the research, interviews, and documented it. To preserve sayur ares, some points need to be improved to increase human resources, management, and promotion in order sayur ares be known by tourists. Keywords: Sayur Ares, Sasak, Culinary, Promotion